Exploring the neuroprotective and alerting effects of modafinil in multiple sclerosis and experimental autoimmune encephalomyelitis - Bibani, Rashid Hamid (2013)
Multiple sclerosis (MS) is the most common demyelinating disease. It is characterised by a great variety of neurological deficits, which most commonly present initially in a relapsing remitting fashion and then take on a gradually progressive course. MS is incurable, since present medications do not counteract progression of the disease. Therefore, an additional strategy aims to focus on prevention of the neuronal loss in an attempt to stop or slow down the progression of the disease.